A Study On The Relationship Between Affective Experience Of New Media Arts And The Physical Gallery - Amir Sharji, Elyna; Forest, Lim Yan Peng; Peter , Charles Woods (2014)

(untitled)
Recently, emergence of new media arts and technology has seen an increase in many related fields of art and design. New Media Art are technology based works which range from mixed media, video and film, digital imaging and performance, photography, film and video, while digital media works are computer-based still or moving images with or without sound. The outputs can be printed on hard copy, displayed on computer monitors, or projected onto a screen and they combine to communicate the intended message and interact with the audience through various media and techniques. As knowledge and technology progress, these newly developed disciplines require suitable physical exhibition space in order for visitors to gain maximum experience from the displayed art work. Thus it is deemed aptly appropriate in the timely discussion among researchers and practitioners to address issues in curating, presenting and exhibiting new media art which challenges the conventional customary method of presentation and documentation. The main objective of this study will therefore to find out whether physical spatial configurations have effects on the affective experience of new media arts content and technology. Observation and survey will be carried out on several presentations of media art in the gallery on how visitors interact and connect with the art work. The gallery space will be determined through space setup, arrangement and plan configuration based on architectural design layout for galleries. This includes partition walls, screens for projection, exhibition furniture (pedestals), lighting, and others to accommodate content such as projection displays, touch screen computers and display panels and others. The findings from this study will be a contribution to artists, designers, researchers and interested parties in the creative realm with the inspiration to encourage a growth of new media art form in conveying intended messages.